Unlocking biochar impacts on abiotic stress dynamics: a systematic review of soil quality and crop improvement - Rathinapriya, Periyasamy; Maharajan, Theivanayagam; Jothi, Ravi; Prabakaran, Mayakrishnan; Lee, In-Bog; Yi, Pyoung-Ho; Jeong, Seung Tak (Frontiers in Plant Science, 2025)
Global agricultural challenges, especially soil degradation caused by abiotic stresses, significantly reduce crop productivity and require innovative solutions. Biochar (BC), a biodegradable product derived from agricultural and forestry residues, has been proven to significantly enhance soil quality. Although its benefits for improving soil properties are well-documented, the potential of BC to mitigate various abiotic stresses-such as drought, salinity, and heavy metal toxicity-and its effect on plant traits need further exploration. This review aims to elucidate BC production by highlighting primary feedstock’s and synthesis techniques, and examining its role in boosting soil decomposition efficiency and fertility, which are pivotal for sustainable crop growth. This review also discuss how BC can enhance the nutritional and chemical properties of soil under different abiotic stress conditions, emphasizing its capacity to foster crop growth and development in adverse environments. Furthermore, this article serves as a comprehensive resource for agricultural researchers in understanding the importance of BC in promoting sustainable agriculture, and addressing environmental challenges. Ultimately, this review highlights critical knowledge gaps and proposes future research avenues on the bio-protective properties of BC against various abiotic stresses, paving the way for the commercialization of BC applications on a large scale with cutting-edge technologies.